Investing peacefully: A global overview of socially responsible investing - (:unkn) unknown (Springer-Verlag Berlin Heidelberg, 2013)
The term 'Socially responsible investing (SRI)' has become increasingly popular since the 1980s. It's becoming one of the trendiest investment approaches in the world especially after the financial crises of recent times. Socially responsible investing is not only interesting for the investors but also for companies and governments of different countries. SRI allows people to invest their funds based on their own personal ethical and moral values. These investments are mostly used to make positive contributions to society in economic, social and environmental terms. Financial intermediaries are finding it harder and socially unacceptable to justify investing in companies which care less about the environment. There are not many socially irresponsible companies left in any event. Financial intermediaries, particularly banks should prolong their goals like making long-lasting profits and maximizing their stock values, but they should also consider protecting their reputation as well as their credibility by supporting socially responsible companies since good reputation means a lot in modern banking. This chapter seeks to demonstrate the importance of ethics and social responsibility in financial markets and to discuss the notion of 'socially responsible investing'. It traces the history of SRIs from its origins, discusses the benefits of Socially Responsible Investing (SRI) and finally discusses the contributions of SRI Indexes and states Turkey's position in SRI. © 2014 Springer-Verlag Berlin Heidelberg. All rights are reserved.